Managed Multi-strata Tree + Crop Systems: An Agroecological Marvel - Nair, P. K. Ramachandran (Frontiers in Environmental Science, 2017)
Today, when the emphasis on single-species production systems that is cardinal to agricultural and forestry programs the world over has resulted in serious ecosystem imbalances, the virtues of the time-tested practice of growing different species together as in managed Multi-strata Tree + Crop (MTC) systems deserve serious attention. The coconut-palm-based multispecies systems in tropical homegardens and shaded perennial systems are just two such systems. A fundamental ecological principle of these systems is niche complementarity, which implies that systems that are structurally and functionally more complex than crop- or tree monocultures result in greater efficiency of resource (nutrients, light, and water) capture and utilization. Others include spatial and temporal heterogeneity, perennialism, and structural and functional diversity. Unexplored or under-exploited areas of benefits of MTC systems include their ecosystem services such as carbon storage, climate regulation, and biodiversity conservation. These multispecies integrated systems indeed represent an agroecological marvel, the principles of which could be utilized in the design of sustainable as well as productive agroecosystems. Environmental and ecological specificity of MTC systems, however, is a unique feature that restricts their comparison with other land-use systems and extrapolation of the management features used in one location to another.